Sustainable development of Tasik Kenyir eco-tourism using system dynamic - Ibrahim, Prof. Datuk Dr. Yahaya (Springer International Publishing, 2019)
The sustainable development of Tasik Kenyir eco-tourism depends on the availibility of spatially explicit information on the state and trends of ecosystems and their services. Thus, we develop an interactive dynamic model of Tasik Kenyir Eco-Tourism that links ecological and economic systems, and generated the effects of the short and long terms besides to determine the direction of development and conservation in Tasik Kenyir development policies. In this study, Tasik Kenyir eco-tourism coins Macro Management Framework for Tasik Kenyir Tourism Dynamics consist of four different subsystem; Toursim Activity, Development of Tasik Kenyir (infrastucture and tourism activities), Waste Generated and Environment Sustainability (flora and fauna). The Model developed reveals that sustainable development of Tasik Kenyir eco-tourism requires continuous prolonged effort and insight towards creating a balance between social, economic and environmental developments. © Springer Nature Switzerland AG 2019.